PENGARUH WILAYATUL HISBAH TERHADAP PELANGGARAN AQIDAH DI KABUPATEN ACEH TAMIANG - Hasnah Nasution; Endang Ekowati; Wisda Pangesti (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2020)
This study aims to determine how the influence of the existence of Wilayatul Hisbah on the good an bad behavior of the community in Aceh Tamiang district. The research method used is descriptive qualitative, namely by parsing, explaining, and describing the close problems in the study. Data collection techniques were carried out by observation, interviews involving Wilayatul Hisbah, the community, border preachers and several members of the village mosque youth and documentation. Data analysis techniques in this study were qualitative data analysis techniques using adjusted effectiveness indicators and the analized through data collection, reduction, presentation, and data collection stages. This research was conducted at the Wilayatul Hisbah office Aceh Tamiang Regency and the community.  Since the implementation of Islamic law in Aceh province, the community must be more careful abaout committing violations that have been determined by the government in Aceh Tamiang district. One of the qanuns is qanun number 11 of 2002 concerning aqidah, worship, syi’ar Islam. Wilayatul Hisbah himself had a very important task as a major role in implementing the qanun. As we all know, every time there is a rule there is always someone who commits a violation, but at least with the existence of strict rules andsanctions the offender will be ashamed to commit the same violation.Keywords : Influence, Wilayatul Hisbah, Violations of Aqidah.